[tex]\displaystyle\bf\\Cos60^\circ Cos15^\circ+Sin60^\circ Sin15^\circ=Cos\Big(60^\circ-15^\circ\Big)=Cos45^\circ=\frac{\sqrt{2} }{2}[/tex]
При решении была применена формула косинуса разности
двух углов :
[tex]\displaystyle\bf\\Cos\alpha Cos\beta +Sin\alpha Sin\beta =Cos(\alpha -\beta )[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
[tex]\displaystyle\bf\\Cos60^\circ Cos15^\circ+Sin60^\circ Sin15^\circ=Cos\Big(60^\circ-15^\circ\Big)=Cos45^\circ=\frac{\sqrt{2} }{2}[/tex]
При решении была применена формула косинуса разности
двух углов :
[tex]\displaystyle\bf\\Cos\alpha Cos\beta +Sin\alpha Sin\beta =Cos(\alpha -\beta )[/tex]